Africanising scholarship: The case of UDW, Natal and UKZN postgraduate educational research (1995–2004) - Karlsson, J; Pillay, G (South African Journal of Higher Education, 2011)
In 2004 the universities of Durban-Westville and Natal merged as part of the national restructuring of higher education in South Africa. These institutions’ faculties and schools of education were, arguably, centres of excellence for research in adult education, teacher education and professional development, mathematics education and gender in education. In its institutional tagline of ‘the premier university of African Scholarship’, the University of KwaZulu-Natal (UKZN) expressed a vision that marked a significant departure from the past. Questions about the meaning of African Scholarship lead the authors to explore how the former institutions’ postgraduate research constitutes a gene pool that already included strands of the central concept in the merged institution’s vision statement. This article explores the postgraduate educational research output stored in the PPER archive from the University of KwaZulu-Natal and its former institutions, a body of over 370 theses, with a focus on the Doctoral theses. We describe how the earlier and current institutions’ key areas of research foci manifest in these theses and critically interrogate the research output i.e. how the ‘ancestor’ institutions’ postgraduate research might have anticipated the UKZN vision. We argue that the postgraduate education research from the two ‘ancestor’ institutions shows evidence of similar formative DNA-like strands to African Scholarship, and were a necessary precondition and preparatory stage for UKZN’s emergence and adoption of an African Scholarship vision in 2004.